Implementing Cybergogy as a Collaborative Approach to Online Islamic Education in the Digital Era - M.Ahmad Jamaluddin zamzami; Hanun Asrohah Asrohah; Husniyatus Salamah Zainiyati Zainiyati (Jurnal Educative: Journal of Educational Studies, 2025)
The advancement of digital technology has significantly transformed the landscape of education, including Islamic Religious Education (Pendidikan Agama Islam, PAI). Amidst the challenges of online learning, which often promote individualistic learning and limited social interaction, the cybergogy approach emerges as a pedagogical strategy that considers emotional engagement, social learning, and cognitive construction within virtual environments. This study aims to examine cybergogy as a strategy to enhance students' digital collaboration in cross-cultural PAI learning in the digital era. This study focuses on two main questions: first, how can the concept of Cybergogy be introduced through Islamic religious education?; and second, how can these concepts be applied in an Islamic educational environment?. This study employs a Systematic Literature Review (SLR) approach, drawing on the principles of a Systematic Mapping Study (SMS). Implementing cybergogy in online PAI learning can enhance students' collaborative engagement through structured instructional design, the use of digital platforms and social media, project-based learning models, and active teacher facilitation. Additionally, this strategy is capable of fostering cross-cultural learning spaces that enrich students' religious and social perspectives. However, the application of cybergogy faces several challenges, including technological access gaps, teacher readiness, and cultural sensitivity, which must be addressed systematically. Therefore, cybergogy holds significant potential to promote collaborative, adaptive, and contextual Islamic education in the digital era.